Ballerina’s voor de vrede. De Vereniging Nederland-USSR importeert sovjetcultuur (1947-1967) - Schrevel, M. (BMGN - Low Countries Historical Review, 2001)
Ballerinas for Peace: The Import of Soviet Culture by the Dutch-Soviet Friendship Society (1947-1967) This article reviews the post-war history of the Dutch-Soviet Friendship Society as well as the apparent lack of pro-Sovietism in large segments of the Dutch communist movement (1947-1997). The Dutch Communist Party (CPN) reestablished the Friendship Society as late as March 1947, at a time when the sympathy of the general public towards the USSR had faded away. It treated its own suborganisation with scepticism and mistrust. Twice, in 1956 and in 1963, party leader De Groot tried to liquidate the society altogether, but his attempts were in vain. Pro-Sovietism in Holland was confined to this Moscow-subsidised Society. Dutch communists could not integrate Soviet culture into their lives: The return to patriotism, militarism and traditional values in the USSR under Stalin did not appeal to them.